Intersectionality in Neurodevelopmental Disorders: A Literature Review on Co-Occurrence of Autism Spectrum Disorder and Attention-Deficit/Hyperactivity Disorder - Examining Therapeutic Approaches and Interventions - Baladaniya, Maheshkumar; Baldania, Shraddha (International Journal of Health Sciences, 2024)
Purpose: To examine the intersectionality between autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD), focusing on the latest research into their co-occurrence, potential shared mechanisms, and implications for diagnosis and treatment. Methodology: A comprehensive literature search was conducted, focusing on studies published within the last 3-4 years on the comorbidity and intersection of traits between ASD and ADHD. Findings: Results reveal high rates of co-occurrence, with 30-80% of individuals with ASD also meeting criteria for ADHD. There appear to be shared genetic, environmental, cognitive, and neural mechanisms contributing to both disorders, potentially explaining this overlap. Despite the frequent co-occurrence, ASD and ADHD present distinct symptom profiles and behavioural challenges. Unique Contribution to Theory, Practice, and Policy: Cognitive-behavioural therapy, social skills training, parental training programs, and stimulant medications are supported as evidence-based approaches for treating both ASD and ADHD. Targeting common mechanisms through combined treatment plans shows promise for improving outcomes. However, more research is needed to develop integrated, personalized treatment models tailored to the specific needs of this substantial subgroup of patients with neurodevelopmental disorders. The intersection between ASD and ADHD traits warrants deeper investigation to better characterize overlapping and disorder-specific phenotypes, guiding targeted treatments.